Ragam Bahasa Dalam Komentar Netizen Terhadap Publik Figur Laura Meizani Mawardi (Lolly) di Platform Media Sosial Instagram: Language Variety in Netizen Comments on Public Figure Laura Meizani Mawardi (Lolly) on the Instagram Social Media Platform - Yulianti, Desiana Ayu; Nugrahaningtyas, Nesya Sekar; Wahid, Nur; Ramadhan, M. Zhafran; Ladyna , Nuke (KIRANA : Social Science Journal, 2025)
This study aims to analyze the language varieties used in netizen comments on public figure Laura Meizani Mawardi (Lolly) on the Instagram social media platform. The research focuses on identifying the language variety, characteristics, and sociolinguistic context behind the comments. The research method used is a descriptive qualitative approach with data collection techniques through documentation and observation of Lolly’s Instagram account comments. Data analysis was conducted by examining linguistic aspects, including informal language varieties, the use of prokemic language, code mixing, and other linguistic variations. The results show that netizen comments show the complexity of language use influenced by social factors, age, cultural background, and the context of interaction on social media. The dominant language variety is slang, characterised by abbreviations, emoticons, and expressions that tend to be free and limitless. This research contributes to understanding the dynamics of communication on social media and the language phenomenon that develops among internet users.